Central metabolism of functionally heterogeneous mesenchymal stromal cells - Barilani, Mario (Sci Rep, 2019)
Metabolism and mitochondrial biology have gained a prominent role as determinants of stem cell fate and function. In the context of regenerative medicine, innovative parameters predictive of therapeutic efficacy could be drawn from the association of metabolic or mitochondrial parameters to different degrees of stemness and differentiation potentials. Herein, this possibility was addressed in human mesenchymal stromal/stem cells (hMSC) previously shown to differ in lifespan and telomere length. First, these hMSC were shown to possess significantly distinct proliferation rate, senescence status and differentiation capacity. More potential hMSC were associated to higher mitochondrial (mt) DNA copy number and lower mtDNA methylation. In addition, they showed higher expression levels of oxidative phosphorylation subunits. Consistently, they exhibited higher coupled oxygen consumption rate and lower transcription of glycolysis-related genes, glucose consumption and lactate production. All these data pointed at oxidative phosphorylation-based central metabolism as a feature of higher stemness-associated hMSC phenotypes. Consistently, reduction of mitochondrial activity by complex I and III inhibitors in higher stemness-associated hMSC triggered senescence. Finally, functionally higher stemness-associated hMSC showed metabolic plasticity when challenged by glucose or glutamine shortage, which mimic bioenergetics switches that hMSC must undergo after transplantation or during self-renewal and differentiation. Altogether, these results hint at metabolic and mitochondrial parameters that could be implemented to identify stem cells endowed with superior growth and differentiation potential.